Opportunities and applications of smart contracts: A vision from the business, academic and scientific literature - Guardado, Rubén Trejo; Carmona, Eduardo Alejandro; Verver y Vargas, Herlinda Goretti López; Hernández, Iván Saúl Jiménez; Martínez, Norma Guadalupe Pérez; Trejo, Blanca Yasmin Vázquez (Iberoamerican Journal of Science Measurement and Communication, 2022)
Objective. In the present work, the bibliographical production referring to smart contracts is reviewed from the business, academic and scientific points of view. The aim is to analyze precisely how the relationship between smart contracts and blockchain occurs to establish a context in both developments. Design/Methodology/Approach. The Scopus database was consulted using the keyword: "smart contract". It was decided to use the SciMAT bibliometric tool for the bibliometric study with the approach based on a joint analysis of words and the h-index to visualize diagrams and thematic areas relatively simply for two periods: 2010-2018 and 2019-2021. Results/Discussion. It was necessary to know the concept of smart contracts for the future of contract law and the digital economy. Some institutions and people will be against considering them as authorized legal alternatives; However, due to the technological advance currently being presented, their development will only be a matter of time. Conclusions. Smart contracts are a technological innovation that, through blockchain technology, carry out transactions safely, quickly and with almost no risk of non-compliance.